18. UPAYA UNODC DALAM MENANGANI NARCOTERRORISM DI AFGHANISTAN PERIODE 2011-2014 - Cimeta, Ribka; Utomo, Tri Cahyo; Paramasatya, Satwika (Journal of International Relations, 2016)
Afghanistan is an area where narcoterrism is happening. In there, Taliban helped to launchthe process of opium production and trade it to the international world and makeAfghanistan as a contributor to the world's largest opium. By using the theory of liberalisminstitutional, the researcher trying to analize UNODC’s effort to combat narcotic and howterrorism group get involved in that issuse. The purpose of this study is to determine thegrowth of opium situation in Afghanistan as well as the intervention of the Taliban, andthe efforts of UNODC to overcome this problem in the period of 2011-2014. The resultsshowed that in UNODC’s effort, they found several obstacles as well as the reality thatshows the increasing amount of opium production program despite all the efforts they didto implements their country programme.